Оптимізація екструзійного процесу отримання сухих харчових продуктів з крахмалевмісної сировини - Зінченко, Марія Георгіївна; Пономаренко, Євгенія Дмитрівна; Манжай, Марія Андріївна (НТУ "ХПІ", 2017)
Показані основні напрямки розвитку екструзійних технологій у харчовій промисловості України – створення нових рецептур сухих харчових продуктів, розробка раціональних режимів їх виробництва. Наведено результати експериментів по оптимізації процесу екструдування збагаченої крахмалевмісної сировини у виробництві картопляних паличок. На підставі отриманих даних розроблено математичну модель, що адекватно описує вплив всіх значущих чинників екструзії на параметр оптимізації – питомі енерговитрати. Встановлено параметри технологічного режиму, що забезпечують мінімальні енергетичні витрати на виробництво екструдата.

The main directions of the development of extrusion technologies in the food industry of Ukraine are shown: the creation of new recipes for dry food products and the development of rational energy-saving production regimes. The results of experiments on optimizing the process of extruding enriched starch-containing raw materials in the production of potato sticks are presented. The specific energy consumption is mostly influenced by the initial humidity of the product, the least is the constructive parameter. On the basis of the data obtained, a mathematical model has been developed that adequately describes the influence of all significant extrusion factors on the optimization parameter – the specific еnergy consumption. The parameters of the technological regime are established, which ensure minimum energy costs for the production of the extrudate. The product obtained as a result of experiments, was studied on a set of indicators that characterize its consumer properties and food and value. Due to the addition to the raw material of skimmed milk extrudate has high protein content and important for the human body of a mineral – calcium, which characterizes its high nutritional value.
Optimization of the extrusion process for obtaining dry food products from starch-containing raw materials
Keywords: експеримент факторний; енергоємність; модель математична; factor experiment; energy intensity; mathematical model